2006
DOI: 10.2337/diacare.29.03.06.dc05-0879
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration as a Risk Factor for the Development of Type 2 Diabetes

Abstract: OBJECTIVE -Short-term partial sleep restriction results in glucose intolerance and insulin resistance. The purpose of this study was to assess the long-term relationship between sleep duration and the incidence of clinical diabetes. RESEARCH DESIGN AND METHODS -A cohort of men from the MassachusettsMale Aging Study without diabetes at baseline (1987)(1988)(1989) were followed until 2004 for the development of diabetes. Average number of hours of sleep per night was grouped into the following categories: Յ5, 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
463
8
15

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 673 publications
(522 citation statements)
references
References 30 publications
36
463
8
15
Order By: Relevance
“…However, increasing evidence from prospective studies shows that disrupted sleep and short sleep duration (under 6.5 hours) are implicated in higher levels of diabetes, obesity, hypertension and mortality (Ayas, White, Al-Delaimy, Manson, Stamfer, Speizer et al, 2003;Ferrie, Shipley, Cappuccio, Brunner, Miller, Kumari et al, 2007;Gangwisch, Heymsfield, Boden-Albala, Buijs, Kreier, Pickering et al, 2007;Patel, Ayas, Malhotra et al, 2004;Tamakoshi & Ohno, 2004;Yaggi, Araujo & McKinlay, 2006). Experimental laboratory research has also shown that chronic sleep deprivation (restricted to 4 hours of sleep for 6 nights) results in significant changes in carbohydrate metabolism, decreased glucose tolerance, elevated evening cortisol levels and increased sympathetic activity, indicating that sleep loss can increase 'allostatic load', facilitating the development of chronic conditions, such as obesity, diabetes and hypertension .…”
Section: Ses Sleep Problems and Healthmentioning
confidence: 99%
“…However, increasing evidence from prospective studies shows that disrupted sleep and short sleep duration (under 6.5 hours) are implicated in higher levels of diabetes, obesity, hypertension and mortality (Ayas, White, Al-Delaimy, Manson, Stamfer, Speizer et al, 2003;Ferrie, Shipley, Cappuccio, Brunner, Miller, Kumari et al, 2007;Gangwisch, Heymsfield, Boden-Albala, Buijs, Kreier, Pickering et al, 2007;Patel, Ayas, Malhotra et al, 2004;Tamakoshi & Ohno, 2004;Yaggi, Araujo & McKinlay, 2006). Experimental laboratory research has also shown that chronic sleep deprivation (restricted to 4 hours of sleep for 6 nights) results in significant changes in carbohydrate metabolism, decreased glucose tolerance, elevated evening cortisol levels and increased sympathetic activity, indicating that sleep loss can increase 'allostatic load', facilitating the development of chronic conditions, such as obesity, diabetes and hypertension .…”
Section: Ses Sleep Problems and Healthmentioning
confidence: 99%
“…[54][55][56] A growing body of epidemiological evidence supports an association between short sleep duration and the risk of obesity [57][58][59][60][61] and type 2 diabetes. [62][63][64][65][66] The potential mechanisms by which sleep deprivation may predispose to obesity are: (1) an alteration of the neuroendocrine control of appetite characterized by a decrease in the levels of the anorexigenic hormone leptin and an increase in the levels of the orexigenic hormone ghrelin; (2) an increased opportunity to eat; (3) an altered thermoregulation; and (4) an increased fatigue leading to reductions in physical activity. 67 Furthermore, physiological data suggest that short-term partial sleep restriction leads to striking alterations in metabolic function including decreased carbohydrate tolerance and insulin resistance.…”
Section: Short Sleep Duration: Association With Glucose Homeostasismentioning
confidence: 99%
“…Sleep duration has recently been recognized as a novel risk factor for type 2 diabetes. Short or long sleep duration was associated with type 2 diabetes [2][3][4][5]. Obesity, in particular abdominal obesity, is also very strongly related to the development of type 2 diabetes [6].…”
Section: Introductionmentioning
confidence: 99%